M. Bachtino chronotopas: tarp epistemologijos ir sociokonstruktyvizmo. - Barusevičius, Dominykas (Problems / Problemos, 2022)
This paper raises the hypothesis that M. Bakhtin's creative category of chronotope is within the dynamic of epistemology and socio-constructivism. To this end, two philosophical conceptions are analyzed: Bakhtin's theory of chronotope as a formally constitutive category of literature and Kant's transcendental aesthetics and transcendental schematism. This comparative analysis shows that chronotope surpasses its primary field of literary analysis and is interpretable not only as an epistemological category which determines the sense experience of the observer, but also as socio-constructivist category which provides reality with an image of a totality of symbolic social institutes. In this way, it is proposed to understand the concept of reality as the multidimensional image.